A fluência digital e a utilização da robótica educacional mediante a abordagem do aprender fazendo e do brincar com crianças - Azevêdo , Edjane Mikaelly Silva de (2018)
The present work is a qualitative research carried out in a school of the municipal teaching network in the city of Cruzeta / RN. It aims in general to analyzing how the process of learning by doing and playing with the children of programming languages and robotics workshop took place. They were used as research tools observations, filming and field diary were used as research instruments, using the descriptive-exploratory methodology, articulating evidenced theory and practice, learning by doing and playing. During the research, for the field to be constructed, a systematic literature review was carried out in some digital databases, so that it was possible to analyze the state of the art about the use of Scratch and educational robotics, as well as to identify the gaps present in this regard. The research is organized in six chapters, where the contextualization, the construction of the field, the conceptualization of logic and the programming language in a broad sense, as well as the Scratch language in the educational context are being approached as an interdisciplinary tool, the educational experiences involving digital fluency, robotics, educational robotics and its use in education, play as a learning resource, methodological processes, the realization of the workshop, as well as the discussion of data collection. Through the analysis of the data, it was observed that Scratch and educational robotics contributed to the development of competences, such as authorship, criticality and autonomy, creativity, teamwork and digital fluency, besides having provided proposals that led the participants to effective terms of becoming digitally included